Cognitive Behavior Therapy for Dependent Personality Disorder: a Case Report (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
This paper reports a case of Dependent Personality Disorder (DPD) treated with Cognitive-Behavior Therapy (CBT).A24 years old female college student was treated with 24 sessions of CBT, which included the use of interviews, the Beck Depression Inventory, the Trait State Anxiety Inventory and CBT techniques. The patient's main complaints, history, data about family functioning, treatment plans and patients motivation regarding treatment, dysfunctional beliefs about diagnosis, coping strategies and autonomy training were discussed during treatment. The main results of the treatment were an important reduction onDPDand depression symptoms, and the development of a behavioral and cognitive repertoire which improved her psychosocial functioning. The use of CBT on the management of DPD, the comorbidity ofDPDand depression e the positive results of the treatment support the current literature about the problem.